CONTRACEPTIVE INCREASING CONTRACEPTIVE USE DURING THE COVID-19 at HARAPAN BUNDA CLINIC MEDAN POLONIA - Mastaida Tambun SST. M.K.M; Eva Ratna Dewi; Anggriani Silitonga; Ime Lestari; AZzara AZzara (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
The Covid-19 pandemic, besides having an impact on the economy, education and society, also impacts on health, one of which is impact on women's reproductive health services, reproductive health services for women are a form of necessity or cannot be postponed. Many women face several changes as a result of social and physical distancing, including for their reproductive health checks. One of these services is the use of contraceptives. Contraceptive use during The covid-19 pandemic is one of the efforts that must be done in couples of childbearing age (PUS) which are expected to postpone pregnancy before the covid-19 pandemic. health workers continue to monitor the use of contraception for women's reproductive health.